2015
DOI: 10.1534/genetics.115.181214
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Notch Signaling by an Evolutionary Conserved DEAD Box RNA Helicase, Maheshvara in Drosophila melanogaster

Abstract: Notch signaling is an evolutionary conserved process that influences cell fate determination, cell proliferation, and cell death in a context-dependent manner. Notch signaling is fine-tuned at multiple levels and misregulation of Notch has been implicated in a variety of human diseases. We have characterized maheshvara (mahe), a novel gene in Drosophila melanogaster that encodes a putative DEAD box protein that is highly conserved across taxa and belongs to the largest group of RNA helicase. A dynamic pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Consistent with the well-documented role of RNA helicases in oogenesis and fertility (87,(123)(124)(125)(126), we identified two putative DEAD-box helicases, CG10077 and Mahe (Maheshvara). While CG10077 is an ortholog of human DDX5, Mahe is an evolutionary conserved regulator of Notch signaling (127). We could recapitulate the interaction of Mahe with both Hrp48 and Glo, and CG10077 with Glo in our co-IP assay.…”
Section: Identification Of Novel Genes With a Potential Role In Drosomentioning
confidence: 76%
“…Consistent with the well-documented role of RNA helicases in oogenesis and fertility (87,(123)(124)(125)(126), we identified two putative DEAD-box helicases, CG10077 and Mahe (Maheshvara). While CG10077 is an ortholog of human DDX5, Mahe is an evolutionary conserved regulator of Notch signaling (127). We could recapitulate the interaction of Mahe with both Hrp48 and Glo, and CG10077 with Glo in our co-IP assay.…”
Section: Identification Of Novel Genes With a Potential Role In Drosomentioning
confidence: 76%
“…Dx binds to the ANK repeats of Notch ICD via its N-terminal Notch-binding domain (Matsuno et al 1995). Different genetic and biochemical analyses suggest that Drosophila Dx, similar to mammalian Dx homologs, acts as a context-dependent modulator of Notch signaling (Diederich et al 1994;Matsuno et al 1995Matsuno et al , 1998Kishi et al 2001;Mukherjee et al 2005;Mishra et al 2014;Surabhi et al 2015). In Drosophila, Dx alone can positively regulate Notch signaling (Matsuno et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was revealed that Shurb, a component of the ESCRT-III (endosomal sorting complexes required for transport-III) complex, modulates the Dx-Krz synergy (Hori et al 2011). Recent studies have also shown that Dx together with TRAF6 (a direct interactor of Notch) or Mahe (an RNA-binding protein) can downregulate the Notch pathway (Mishra et al 2014;Surabhi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila stocks used for analysis were w 1118 (wild‐type), mahe EP1347 (hypomorphic allele for mahe ), and EP Δmahe d08059 (null mutant for mahe ). Embryo collection and immunostaining was done as described previously (Surabhi et al., ). Primary antibodies used were rabbit anti‐Mahe, 1:300; rat anti‐ELAV, 1:200; and mouse anti‐22c10, 1:100.…”
mentioning
confidence: 99%